Adaptability Evaluation of High-Density Kill Fluid for Ultra-Deep and Ultra-High Temperature Well Testing in Tarim Oilfield - Junyan Liu; Lili Li; Shuang Liu; Yan Ye; Sihan Cheng; Kun Wang; Lang Wang; Zhenjiang Wu; Jun Wu (Energies)
To address the insufficient long-term stability of kill fluids in ultra-deep, ultra-high-temperature wells in the Tarim Oilfield, this study systematically evaluates the adaptability of high-density kill fluids under high-temperature and prolonged static aging conditions, with a focus on identifying dominant settling mechanisms. The correlation between the microstructure and macroscopic properties of kill fluids was elucidated through particle size distribution analysis, scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and rheological characterization. A quantitative grading criterion for settling stability was established using settlement values and the falling rod method. Key findings demonstrate that low-density kill fluids (1.4–1.6 g/cm3) retained rheological stability after 20 days of aging at 220 °C, fulfilling the ≥20-day operational requirements for ultra-deep well testing. In contrast, high-density systems (1.9 g/cm3) exhibited severe particle aggregation after 15 days under identical conditions, with the yield stress-to-plastic viscosity ratio dropping below 0.10 and suspension capacity deteriorating. The apparent viscosity of ultrafine barite-weighted kill fluid increases with temperature, and its settling value is positively correlated with aging time and temperature. The settling mechanism of ultrafine barite-based kill fluids was attributed to reduced surface charge density caused by the decarboxylation of polyacrylate dispersants, which diminished interparticle electrostatic repulsion. The developed “settlement value vs. falling rod time” correlation model and grading criteria lay a theoretical foundation for optimizing kill fluid formulations and evaluating field performance in ultra-high-temperature wells, offering critical engineering insights to ensure safe deep hydrocarbon testing operations.